Active transportation and the built environment of a mid-size global south city. (February 2023) - Rahman, Md. Mokhlesur; Upaul, Sharfan; Thill, Jean-Claude; Rahman, Mahinur
Highlights: Estimation of impacts of the built environment on active transportation in a mid-size Global South city. Compactness and condition of sidewalks increase walking, while decreasing bicycling. Adequate street width to accommodate lanes for active transport increases active travel. Built environment is more influential than people's socioeconomic attributes on active travel. We recommend a polycentric city structure to encourage active travel. Abstract: This study measures the existing condition of the built environment in the mid-size city of Khulna, Bangladesh and investigates its impacts on active transportation. Although the built environment is found to be rather conducive to active travel, the use of active transportation is depressed by the abundance of low-cost for-hire motorized vehicles and other structural and operational considerations. A Structural Equation Modeling framework is used to investigate the relationships between the built environment and active transportation. The model shows that compactness and the condition of sidewalks significantly increase walking propensity, while decreasing bicycling. Roadway infrastructure reduces walking and bicycling due to wider options of motorized vehicles. Additionally, longer travel distance and higher travel cost significantly reduce people's walking tendency. The study demonstrates that the built environment has a strong effect on active transportation, particularly on walking, compared to people's socioeconomic and personal attributes. The study findings are useful for policy formulation supporting a range of mobility options in mid-size Global South cities.